Hadis Palsu Di Media Sosial Persepsi Mahasiswa Fakultas Syariah UIN Bukittinggi - Febri Yeni; Gonsales Gonsales (Jurnal Ulunnuha, 2022)
The polemic of fake hadiths is growing with unlimited access to information through social media. Many posts were found containing popular hadiths, but it turned out that Maudhu' or fake. Falsifying hadiths and spreading them is haram except to explain their falsity. For this reason, the introduction of the concept of fake hadith is a key discussion in hadith science courses. This study highlights students' perceptions and attitudes towards the phenomenon of fake hadiths on social media with the aim of measuring students' understanding of the concept of fake hadiths and knowing students' attitudes towards fake hadiths on social media. The object of research is students outside the hadith science study program. The reason for choosing the Sharia Faculty of UIN Bukittinggi was because it had a larger portion of learning hadith compared to other faculties. This type of research is field research using mix research methods, namely a combination of quantitative and qualitative research. The research sample consisted of 118 students who were selected using the proportional random sampling technique. The results showed that the score of students' understanding of the indicators of the theory of fake hadith was 65.97% in the sufficient category, the indicator for falsification of hadith in sanad was 72.39% in the sufficient category, the indicator for falsification in matan was 80.77% in the good category, the indicator for fake hadith in the media the social score is 68.26% in the sufficient category, and the attitude indicator towards fake hadith is 80.24% in the good category. The attitude of students towards fake hadiths on social media includes, firstly, tracing the truth of hadiths. Second, be careful and will not share a hadith that is clearly false. Third, provide an explanation of the falsity of a hadith